2017
DOI: 10.1038/s41598-017-12866-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of antibiotic and probiotic feed additives for Gallus gallus domesticus

Abstract: Antibiotics in feed select for resistant strains and is thus a threat to human health. In this study, the effect of a multi-strain probiotic and antibiotics on the growth and health of broilers was studied. Equal numbers of broilers received on a daily basis either a multi-strain probiotic or a combination of sulphadiazine, colistin and trimethoprim, whereas the control group received standard feed. The villi of immature broilers (19 days old) administered antibiotics had a larger surface area and their lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 109 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…probiotics that lead to increase in relative lymphoid organ weights (such as spleen). This assumption is supported by report of Neveling et al (2017), who reported higher lymphocytes level in birds after dietary supplementation with probiotics.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…probiotics that lead to increase in relative lymphoid organ weights (such as spleen). This assumption is supported by report of Neveling et al (2017), who reported higher lymphocytes level in birds after dietary supplementation with probiotics.…”
Section: Discussionsupporting
confidence: 75%
“…Deng et al (2012) also found that dietary Bacillus licheniformis increased villus height in the ileum under heat stress conditions. It is showed that the digestive function of the intestine is related to villi structure and mucosal architecture, which influence absorptive capacity (Sen et al, 2012;Neveling et al, 2017). Moreover, probiotics by shortchain organic acids formation stimulate the proliferation of epithelial cells and lead to increased villus height (Ichikawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Free-range environment can improve egg laying performance, promote feeding activities of chickens, and improve animal welfare. Specific pathogen free (SPF) animals were introduced in the 1960s to reduce disease or infection as a variable not required in their experiments [28]. Today, the overall strategy for most livestock industries is to incubate animals that do not contain infectious agents from sterile livestock or cesarean delivery aseptic techniques for experimental animal models of various diseases [11].…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…All the above might be explained by our ndings that the human disease-related pathways, including cancer, drug resistance, endocrine, and metabolic diseases, infectious diseases were more abundant in the AMX treatment group. Similarly, POL suggested the effect of immune responses and induce disease incidence, including insulin-dependent diabetes, diarrhea, bacterial infections, and translocation using animal models [58][59][60][61][62].…”
Section: Combination Treatment Promote the Increase Of The Human Disementioning
confidence: 99%